A questionnaire to collect unintended effects of transcranial magnetic stimulation: A consensus based approach. (September 2022) - Giustiniani, A.; Vallesi, A.; Oliveri, M.; Tarantino, V.; Ambrosini, E.; Bortoletto, M.; Masina, F.; Busan, P.; Siebner, H.R.; Fadiga, L.; Koch, G.; Leocani, L.; et al.
Highlights: A TMS questionnaire, TMSens_Q, was developed to report secondary effects following TMS application. A Delphi procedure was used to reach a consensus on items among international TMS experts. The TMS questionnaire could improve the quality of data reporting in TMS studies. Abstract: Transcranial magnetic stimulation (TMS) has been widely used in both clinical and research practice. However, TMS might induce unintended sensations and undesired effects as well as serious adverse effects. To date, no shared forms are available to report such unintended effects. This study aimed at developing a questionnaire enabling reporting of TMS unintended effects. A Delphi procedure was applied which allowed consensus among TMS experts. A steering committee nominated a number of experts to be involved in the Delphi procedure. Three rounds were conducted before reaching a consensus. Afterwards, the questionnaire was publicized on the International Federation of Clinical Neurophysiology website to collect further suggestions by the wider scientific community. A last Delphi round was then conducted to obtain consensus on the suggestions collected during the publicization and integrate them in the questionnaire. The procedure resulted in a questionnaire, that is the TMSens_Q, applicable in clinical and research settings. Routine use of the structured TMS questionnaire and standard reporting of unintended TMS effects will help to monitor the safety of TMS, particularly when applying new protocols. It will also improve the quality of data collection as well as the interpretation of experimental findings.